Medications for opioid use disorder during pregnancy: Access and continuity in a state women's prison facility, 2016–2019. (1st March 2022) - Knittel, Andrea K.; Swartzwelder, Rita A.; Zarnick, Samantha; Tsujimoto, Tamy Harumy Moraes; Horne, Timelie; Lin, Feng-Chang; Edwards, James; Amos, Elton; Alexander, James; Thorp, John; Jones, Hendree E.
Abstract: Background: Although medications to treat opioid use disorder (MOUD) are the standard of care during pregnancy, there are many potential gaps in the cascade of care for pregnant people experiencing incarceration. Methods: We conducted a retrospective cohort study of pregnant people with opioid use disorder incarcerated in a Southeastern women's prison from 2016 to 2019. The primary outcomes were access to MOUD during incarceration and continuity in the community. We used descriptive statistics to summarize aspects of our sample and logistic regression to identify predictors of MOUD receipt during incarceration. Results: Of the 279 pregnant people with OUD included in the analysis, only 40.1% ( n  = 112) received MOUD during incarceration, including 67 (59.8%) who received methadone and 45 (40.1%) who received buprenorphine. Less than one-third of the participants were referred to a community MOUD provider ( n  = 83, 30%) on return to the community. Significant predictors of MOUD receipt included medium/close custody level during incarceration, incarceration during the latter portion of the study period, pre-incarceration heroin use, and receipt of pre-incarceration MOUD. Conclusions: Although prisons can serve as an important site of retention in MOUD for some pregnant people, there were substantial gaps in initiation of MOUD and retention in MOUD among pregnant people with OUD imprisoned in the Southeast during the study period. Highlights: Only 40% of eligible pregnant people received either buprenorphine or methadone during incarceration Fewer than one-third were referred for medications for opioid use disorder after incarceration Withdrawal symptoms are common when buprenorphine/ methadone is discontinued postpartum during incarceration